Characterization of an Oleaginous Unicellular Green Microalga, Lobosphaera incisa (Reisigl, 1964) Strain K-1, Isolated From a Tidal Flat in the Yellow Sea, Republic of Korea - Lee, Seungki; Lim, Se Ra; Jeong, Dae Gwin; Kim, Ji Hyung (Frontiers in Microbiology, 2018)
Microalgae are considered as sustainable resources for biofuel production. However, recently the focus on microalgal research has shifted towards the investigation of high-value metabolites for potential pharmaceutical and nutritional applications. Herein, we report the identification of a novel oleaginous green microalga isolated from the Yellow Sea in Korea. We also describe the morphological, molecular, and biochemical characteristics of this microalga. On the basis of microscopic and genetic analyses, the isolate was classified as Lobosphaera incisa (the strain was designated as K-1), and molecular phylogeny revealed that the isolate distinctly differed from the other known L. incisa strains. The microalga could be cultivated in various commercial culture media under a relatively broad range of pH and temperature conditions. We also did a rough and detailed estimation of the different cellular components in the microalga. The composition of arachidonic acid (C20:4ω6) in the lipids of L. incisa strain K-1 was relatively high, similar to that in other strains; however, the K-1 strain had higher proportions of the ω3 series of fatty acids including α-linolenic acid (C18:3ω3) and eicosapentaenoic acid (C20:5ω3), highlighting its uniqueness and strong potential for biotechnological application. To the best of our knowledge, this is the first report on the isolation of L. incisa from Korea as well as from a marine environment; this novel strain might be useful for the production of high-value ω3 and ω6 polyunsaturated fatty acids.